Improving Efficiency in Indonesia's Tax Objection Process: Reducing Bureaucracy and Enhancing Access to the Tax Court - Marmiyati, Marmiyati; Hien, Uddiyana Khoe Keng; Slamet JM, Harjanto; Ka, Pho Seng; Prasetyo, Ponco; Kustanto, Anto (Law Development Journal, 2025)
This paper discusses the inefficiencies in Indonesia's tax objection process, specifically regarding the Objection Letter (Surat Ketetapan Pajak) issued by the Directorate General of Taxes. Taxpayers can file objections if they disagree with the tax determination, as guaranteed by Indonesian tax laws, particularly Law No. 6 of 1983, amended by Law No. 6 of 2023. The process is classified as “quasi-judicial” because the entity adjudicating the objections is part of the same institution involved in the dispute. This often places taxpayers at a disadvantage, with the outcome typically unsatisfactory for them. The law allows the Directorate General of Taxes up to 12 months to issue an objection decision, leading to a total of 21 months from the start of the tax audit to the final decision. Taxpayers can appeal the decision to the Tax Court. The paper concludes that the tax objection process is inefficient in terms of time, effort, and cost. It recommends simplifying the procedure by allowing direct filing of objections after the tax audit, followed by the issuance of the tax determination. This would enable taxpayers to appeal directly to the Tax Court, reducing bureaucratic delays and achieving greater efficiency in terms of time and resources.